The Influence of Work Ability and Organizational Culture on Employee Performance Through Leadership in Malaka Regency Government - Maria Agustina Luruk; Moch. Natsir; Sutriswanto Sutriswanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Regional Secretariat (SEKDA) of Malacca Regency is an assistant element of the district government leadership led by a regional secretary who is under and responsible to the Regent. This study aims to analyze the effect of work ability, organizational culture on employee performance through leadership in the Regional Secretariat (SEKDA) of Malacca Regency. The sample used in this study was 58 employees. The method used is linear regression analysis. The results showed that there was a partially significant effect of work ability, organizational culture and leadership variables on employee performance. The work ability variable has a significant effect on employee performance. Organizational culture has a significant influence on employee performance.